In-silico evidences for binding of Glucokinase activators to EGFR C797S to overcome EGFR resistance obstacle with mutant-selective allosteric inhibition. (June 2018) - Patel, Harun; Pawara, Rahul; Surana, Sanjay
Graphical abstract: Highlights: In-silico evidences for binding of Glucokinase Activators to EGFR C797S. EGFR resistance obstacle of C797S. Mutant-selective allosteric inhibition. Abstract: The tyrosine kinase inhibitors (TKI) against epidermal growth factor receptor ( EGFR ) are generally utilized as a part of patients with non-small cell lung carcinoma (NSCLC). However, EGFR T790M mutation results in resistance to most clinically available EGFR TKIs. Third-generation EGFR TKIs against the T790M mutation has been in active clinical development to triumph the resistance problem; they covalently bind with conserved Cys797 inside the EGFR active site, offering both potency and kinase-selectivity. Third generation drugs target C797, which makes the C797S resistance mutation more subtle. EGFR C797S mutation was accounted to be a main mechanism of resistance to the third-generation inhibitors. The C797S mutation gives off an impression of being an ideal target for conquering the acquired resistance to the third generation inhibitors. We have performed structure based-virtual screening strategies for binding of glucokinase activator to EGFR C797S, which can overcome EGFR resistance impediment with mutant-selective allosteric inhibition towards all kinds of mutant EGFR (T790M, L858R, TMLR) and WT EGFR. The final filter of Lipinski's Rule of Five, Jargan's Rule of Three and in silico ADME predictions gave 23 hits, which conform to Lipinski's rule and Jorgensen's rule and all their pharmacokinetic parameters are inside the appropriate range characterized for human use, in this manner demonstrating their potential as a drug-like molecule.